2003
DOI: 10.1046/j.1365-2710.2003.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Is oral azithromycin effective for the treatment of cyclosporine-induced gingival hyperplasia in cardiac transplant recipients?

Abstract: Anecdotal evidence suggests that azithromycin is effective for the treatment of cyclosporine-induced gingival hyperplasia in solid-organ transplant recipients. We present the cases of two heart transplant patients who insidiously developed gingival hyperplasia, likely because of immunosuppression with cyclosporine, which was treated with azithromycin. Evidence supporting the efficacy of azithromycin in the treatment of cyclosporine-induced gingival hyperplasia in solid organ transplant recipients was searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
10
0
5
Order By: Relevance
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
“…[35606164656667686970727475] It has also been used for treating aplastic anemia,[586073] psoriasis,[62] and Behcet disease. [71] Cyclosporine is known to alter the metabolism of gingival fibroblasts and also upregulates specific growth factors such as platelet-derived growth factor B, thereby causing adverse gingival changes such as overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made by various researchers in their respective studies on CsA-induced GO in animal models[1027] and in humans. [8911262829]…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, administration of Azi resulted in significant regression or inhibition of CsA-induced GO in renal[892628] and cardiac transplant[29] patients, but effect on CsA + Nf induced GO was not evaluated profundity in dental literature. The present study demonstrates that short-term (7 days) course of Azi can effectively inhibit the GO induced by CsA + Nf combination, along with the simultaneous use of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A study of clinical trials revealed benefits of systemic azithromycin in such conditions [41] Hooda and Narula [13] gave azithromycin to their patients with gingival hyperplasia and symptomatic relief was noticed in all patients. They proposed that treatment with azithromycin is inexpensive and effective in short period of time, avoiding gingival surgery in large number of patients.…”
Section: Drug Therapymentioning
confidence: 99%